EFFECTIVE HISTORY IN THE NOVELS TRILOGY OF RARA MENDUT BY Y.B. MANGUNWIJAYA: A GENEALOGICAL STUDY OF MICHEL FOUCAULT - Siti Maisaroh; Fitri Resti Wahyuniarti; Muminin Muminin; Aang Fatihul Islam (RETORIKA: Jurnal Bahasa, Sastra, dan Pengajarannya, 2023)
Trilogy of Rara Mendut’s novels are focused on four things with a working method based on Michel Foucault's genealogical theory which examines past events that can be used to see the present. The results of the study include: 1) the parental care system for children shows that children must receive sufficient attention, affection, and wholehearted care for their mental development; 2) unlimited power has an impact on people's misery, many enemies, leading tends to be cruel, and brings destruction; 3) the nature of a person is influenced by environmental factors; and 4) the essence of serving in real life is not one's superiors or institutions but to the people, especially those who are still suffering.